Performance arte e gênero no tradicionalismo gaúcho - Potrich, Bruna Leticia (2022)
The presented text discusses the Master's research that deals with the creation of a poetics in Performance Art, developed at the PPGART/CAL, of the Federal University of Santa Maria (UFSM), in Contemporary Art. The investigation is part of the Art and Culture research line. The study consisted of how to materialize the creation of a poetics in Performance Art that discusses the gender roles, as well as the power relations circulating over the male/female figures in the scope of gaucho traditionalism, established as an organized movement. In this sense, the aim was also to explore the transversality that contemporary art carries as a potentiator of the artistic creation of the body in the state of the art. The preference for the artistic language Performance Arte was due to this being a phenomenon that encompasses arts, body and communication, characterized by its tendency, among others, of immersion in latent and manifest social issues. The authors Goldberg, Fabião, Taylor and Medeiros support and strengthen performative actions in their theoretical-practical aspects. With regard to gender relations, the theories Scott, Butler and Grossi consolidate the concepts used in the research. To support the discussions on gaucho traditionalism, there are authors such as Brum and Golin. The methodological procedures sought resources and experiences in field research, subsidized by an autoethnographic bias, bringing the performer-researcher closer to the investigated context, in which she was immersed for many years. In this way, the stimuli for the creation of Artistic Performances derive from the materials learned in the field and from the experiences of the artist-researcher in contact with the context. Thus, the path was built to question the chosen question, crossing the creative path of the series of Performances that cover the social and cultural changes of gender roles and power relations, as well as the remnants and cultural behaviors that remain crystallized in gaucho traditionalism. Therefore, we seek to propose a reflection on the figurative role, occupied and performed by the gaucho woman through artistic creation. As a result of this practical-theoretical research, a total of five works were carried out, four of which were video performances and an urban performative intervention that, together, make up the poetic series called Encruzilhadas de Tempo e Vida. It is considered that the path taken through autoethnographic creation can produce unique discourses and transits that, however, connect and sensitize other subjectivities.